Pengaruh Promosi Media Sosial Terhadap Minat Beli Konsumen Kuliner Ayam Square - Faizathul Octavia, Yusi (IRPI Publisher, 2022)
The main objective of this research is to analyze the effect of social media promotion (Instagram & Tiktok) on consumer purchase intention in Ayam Square's culinary business in Mataram City. The population of this study is Ayam Square customers in Mataram City. The sample collection method used is non-probability sampling with a purposive sampling technique. The data used is primary and secondary data. Primary data was collected through a survey of 100 respondents. The data analysis method used is multiple linear regression analysis using the assistance of SPSS version 26. The results of the research show that short video content promoted through video-based social media (Instagram & Tiktok) has a significant impact in increasing consumer purchasing interest in Ayam Square's culinary business. This research shows that promotion through social media has a crucial role in building consumer purchasing interest and helping to increase the profitability of the culinary business.